2018
DOI: 10.26599/tst.2018.9010077
|View full text |Cite
|
Sign up to set email alerts
|

Loading-balance relay-selective strategy based on stochastic dynamic program

Abstract: A Relay-Assisted (RA) network with relay selection is considered as a type of effective technology to improve the spectrum and energy efficiency of a cellular network. However, loading balance of the assisted relay node becomes an inevitable bottleneck in RA network development because users do not follow uniform distribution. Furthermore, the time-varying channel condition of wireless communication is also a major challenge for the RA network with relay selection. To solve these problems and improve the pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The underground wastewater influx is closely related to climate, hydrology, landforms, and mining schedules [28] . The temperature of geothermal energy to be released can be increased along with the mining depth, and the amount of geothermal release is also influenced by environmental factors such as season and climate [29] . In summary, CMAE has great uncertainties and volatilities, which must be carefully treated in the dispatching process.…”
Section: Comentioning
confidence: 99%
See 1 more Smart Citation
“…The underground wastewater influx is closely related to climate, hydrology, landforms, and mining schedules [28] . The temperature of geothermal energy to be released can be increased along with the mining depth, and the amount of geothermal release is also influenced by environmental factors such as season and climate [29] . In summary, CMAE has great uncertainties and volatilities, which must be carefully treated in the dispatching process.…”
Section: Comentioning
confidence: 99%
“…Model with Interval Uncertainty As addressed in Section 3, in our dispatch model, the variables to be optimized include two parts, crisp variables as and the other is the interval ones as , which greatly differ from those in traditional interval dispatch models, as described in Ref. [29]. For traditional interval dispatch models, the intervals are usually known parameters, i.e., the upper and lower limits are determined, and the variables to be optimized are only crisp values in such an interval.…”
Section: Transformation Of Cmies Optimizationmentioning
confidence: 99%
“…Last, the SAFs aims at a single fault in the chip, while existing experiments have shown that the test set that can cover all single faults also has a high coverage rate when multiple faults are being detected [22] . For the generated PMS formulas, SATLike, which is a famous incomplete partial MaxSAT solver based on the dynamic local search [23] approach, is selected in Step (6). In terms of the new set of test patterns, Step (7) confirms that the fault coverage will not decrease.…”
Section: Test Compactionmentioning
confidence: 99%